Mechanical Characterization of Handball Shoes Using Biomechanical Load Spectrums. (2015) - Krumm, Dominik; Gläser, Anne; Schlegel, Gert; Odenwald, Stephan
Abstract: The purpose of this paper was to mechanically characterize handball shoes using biomechanical evaluated load spectrums. In the first step a biomechanical study with 15 experienced amateur handball players was conducted. Within this study the kinematics and kinetics of three typical handball activities, namely sprint, feint and jump shot, were evaluated using an optoelectronic measurement system and a force plate. After determining typical biomechanical load spectrums for handball activities from the collected data, in a second step a sample of nine handball shoes size UK 8 were mechanically tested to characterize their cushioning properties.